Vascular Regeneration and Long Distance Transport of Indole-3-acetic Acid in Coleus Stems - Thompson, Neal P. (1966)
Excision of all leaves and buds of Coleus blumei Benth. plants reduced xylem cell and sieve tube regeneration a highly significant amount around a wound in internode number 5 when compared with regeneration in intact (wounded) plants. Application of indoleacetic acid (IAA-(14)C) to the cut surface of internode number 2 restores regenerative activity around the wound in internode number 5. Radioactivity applied as IAA-(14)C reaches the wound area when applied at the cut surface of inter-node number 2 showing a logarithmic decrease with distance from the point of application. Chromatography showed that radioactivity was located close to the R(F) of IAA as well as near the solvent front. Addition of gibberellic acid to IAA-(14)C did not change the pattern of radioactivity throughout the stem.